The Importance of Professional Training for Establishing Psychological Health Workers - Radoja, Dukata (European Journal of Multidisciplinary Studies, 2017)
Training is an important part of modern European healthcare services and is often cited as a way to improve care quality. Health workers constantly participate in training aimed at enhancing their professional, although often noted lack of training adapted to their specific needs. The purpose of this study was to identify the needs for vocational training that nursing Shkodra need to handle psychologically their patients where specifically the main goal is to recognize the level of practical skills adviser to the profession of a nurse, techniques, application of these skills in hospital settings. Results of the study reported that about 63.3 percent of subject report that they are trained on the techniques of psychological counseling, about 18.5 percent of the subjects are familiar with these training through scientific articles, about 41.1 percent, through announcements made by the Directorate of Public Health, 18.5 percent, via the internet, 16.1 percent are recognized through curricula, 5.6 percent through newspapers. And 87.4 percent of subjects were equipped with skills and techniques to handle the emotional state of patients or their families, while 12.6 percent report that these exercises are not equipped with these skills, as about 90.7 percent of the sample report that would have liked to be trained to enhance their professional skills in dealing with emotional concerns etc.